Robert Ludlum's The Bourne retribution [large type] : a new Jason Bourne novel - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel, 2013)
Jason Bourne's friend Eli Yadin, head of Mossad, learns that Ouyang Jidan, a senior member of China's Politburo, may have been working with a major Mexican drug lord in something far deadlier than drugs. Yadin needs Bourne to investigate. Bourne agrees, but only because he has a personal agenda. Focused on vengeance, Bourne becomes enmeshed in a monstrous worldwide scheme involving the Chinese, Mexicans, and Russians.